2015
DOI: 10.1021/acs.jafc.5b00988
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD-MS Profiling of Polyphenols Responsible for the Yellow-Orange Color in Apple Juices of Different French Cider Apple Varieties

Abstract: The pigments responsible for the yellow-orange coloration of apple juices have remained largely unknown up to now. Four French cider apple juices were produced in conditions similar to those used in the cider-making industry. The oxidized juices, characterized using the CIE L a b parameters, displayed various colors depending on the apple variety and native phenolic composition. HPLC-DAD-MS revealed contrasting pigment profiles related to oxidized tanning and nontanning molecules. The latter were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…Peak 36 was identified as phloretin-xylosyl-glucoside (m/z 567.1675, -4.45 mmu) and Peak 39 was identified as phloridzin (m/z 435.1278, -1.89 mmu). These results are in agreement with the previous studies (Le Deun et al, 2015;Montero et al, 2013;Ramirez-Ambrosi et al, 2013;Vrhovsek et al, 2012). These results provided a preliminary foundation for further metabolomics study.…”
Section: Identification Of the Major Phenolic Compoundssupporting
confidence: 93%
“…Peak 36 was identified as phloretin-xylosyl-glucoside (m/z 567.1675, -4.45 mmu) and Peak 39 was identified as phloridzin (m/z 435.1278, -1.89 mmu). These results are in agreement with the previous studies (Le Deun et al, 2015;Montero et al, 2013;Ramirez-Ambrosi et al, 2013;Vrhovsek et al, 2012). These results provided a preliminary foundation for further metabolomics study.…”
Section: Identification Of the Major Phenolic Compoundssupporting
confidence: 93%
“…According to Orellana-Palma et al 14 the darkening of the color of samples is due to the increase in solids content due to the freeze concentration process; an increase in phenolic compounds also occurred (L* versus TPC, r = −0.98, P < 0.01). According to Le Deun et al 42 the pigments responsible for the color of juices are derived from the oxidation of the colorless native phenols. Therefore, the phenolic profile of the apple variety influences the color of the juice.…”
Section: Color Properties Of the Juices And Cryoconcentratesmentioning
confidence: 99%
“…Chlorogenic acid and flavanols seem to be the main phenolics that are oxidized and contribute to the color of juices. In addition, Le Deun et al 42 and Le Guernevé et al 43 identified yellow pigments from phloretin xyloglucoside and phloridzin oxidation.…”
Section: Color Properties Of the Juices And Cryoconcentratesmentioning
confidence: 99%
“…The only difference in these two molecules is that of the sugarxylose and glucose respectively. 12 (E) Pigments in wine: Pyranoanthocyanins are a class of red wine pigments formed as early as during alcoholic fermentation and also during aging of wine. General pathway involves an anthocyanin and a compound having polarizable double bond, reacting to give rise to a new pyrano ring (D ring in Figure 5) fused to anthocyanin molecule.…”
Section: Pigments Formed As a Results Of Processingmentioning
confidence: 99%